2015
DOI: 10.1111/eve.12334
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of maxillary cheek teeth apical infection caused by patent infundibula in six horses (2007–2013)

Abstract: Summary Six young horses presented with clinical signs of maxillary cheek teeth apical infection (bilateral in 2 horses) that included the presence of rostral maxillary swellings with discharging sinus tracts and were unexpectedly found to have no evidence of endodontic infection in 7 affected teeth. The apical infection of these teeth was attributed to infundibular dysplasia that allowed inoculation of the periapical tissue with contaminated oral contents. Treatment was by debridement and obturation of affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
17
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 24 publications
0
17
0
1
Order By: Relevance
“…As can be seen in the CT scan in Figure 15 in the article by Pearce () and in the CT scan and CT reconstructions in Windley et al . (,b), there can be marked pathology of the apical aspect of the infundibulum with little or no abnormality of the occlusal portion of the infundibulum.…”
mentioning
confidence: 81%
See 3 more Smart Citations
“…As can be seen in the CT scan in Figure 15 in the article by Pearce () and in the CT scan and CT reconstructions in Windley et al . (,b), there can be marked pathology of the apical aspect of the infundibulum with little or no abnormality of the occlusal portion of the infundibulum.…”
mentioning
confidence: 81%
“…Also in this issue, Pearce () reports the staged use of calcium hydroxide and infundibular restoration for treatment of apically infected maxillary cheek teeth in which the underlying aetiology is apical patency of the infundibulum. The infundibula of maxillary cheek teeth have also been recently investigated both in vivo and in extracted teeth with high resolution CT (Windley et al .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A few studies have reported techniques for the treatment of infundibular caries. 7,14 Despite some of the techniques illustrating the difficulty in effective restoration of the caries, restoration still slows down or ceases the progression of the tooth decay.…”
mentioning
confidence: 99%